SCREENING OF THERMOTOLERANT RAGI GENOTYPES AT SEEDLING STAGE USING TIR TECHNIQUE - BABU, D. VENKATESH; P. SUDHAKAR; REDDY, Y. SHARATH KUMAR (The Bioscan, 2013)
Here we report a novel temperature induction response (TIR) technique was standardized for ragi crop. We have standardized the sub lethal i.e. challenging temperatures 38-54ºC (for 5 hours) and lethal temperatures as 57ºC (for 2 hours). Using this standardized TIR protocol, highly thermotolerant ragi genotypes were screened from 100 ragi germplasm. Among the genotypes, GP-160 and GP-27 showed highest thermotolerance in terms of 100 per cent seedlings survival and no reduction in root and shoot growth.GP-153, GP-149 and GP-25 also showed higher thermotolerance in terms of 90% seedlings survival and no reduction in root and shoot growth. These genotypes have intrinsic heat tolerance and they can be explored as donar source in breeding programme aimed for global warming.